Avatāro ane avatāravāda : traṇa vyākhyāno - Māṅkaḍa, Dolararāya Raṃ (Śeṭha Bho. Je. Adhyayana-Saṃśodhana Vidyābhavana, 1978)
On the concept of Avatāra (incarnation) as propounded by various Hindu scriptures and religious works.